Descending-sigmoid colon flexure – An important but surprisingly ignored landmark - Wozniak, Slawomir; Pawlus, Aleksander; Grzelak, Joanna; Chobotow, Slawomir; Paulsen, Friedrich; Olchowy, Cyprian; Zaleska-Dorobisz, Urszula (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Background: In invasive examinations of the colon, e.g. colonoscopy, the tortuosity of the colon is a crucial factor for successful completion of the procedure. If adjacent segments of the colon bend at acute angles (under 90°), endoscopy may become difficult and troublesome. Methods: We retrospectively enroled 227 individuals (96 female, 131 male) who underwent abdominopelvic computed tomography examination. For inclusion, subjects were required to have a negative history for colonic disease and abdominopelvic surgery. We measured the angle between the descending colon and the proximal part of the sigmoid (in degrees). In addition, the position of the descending-sigmoid flexure was assessed in relation to the left anterior superior iliac spine, the median plane, and anterior aspect of the 5th lumbar vertebra (in mm). The study protocol was reviewed and approved by the local ethics committee. Results: We visualised the descending-sigmoid flexure in all 227 subjects. In one third of cases, the flexure formed an angle smaller than/or 90°. In females, this landmark (mean ± standard deviation) was located 30.2 ± 8.4 mm from the left anterior superior iliac spine, 88.6 ± 14.2 mm from the median plane, and 115.4 ± 21.4 mm from the anterior aspect of the 5th lumbar vertebra. In males, the dimensions were: 32.1 ± 12.8 mm, 97.6 ± 15.8 mm, and 123.9 ± 22.9 mm, respectively. This landmark distance remained constant from the left anterior superior iliac spine regardless of subject age, height and weight. The other measured distances were related to age, height, weight or BMI. Conclusions: The descending-sigmoid flexure is an important landmark in large intestine morphology situated approximately width of two fingers (3 cm) from the left anterior superior iliac spine and one hand width (9–10 cm) from the median plane. In approximately one third of the subjects, the flexure formed an angle of less than/or 90°, which can cause a problem during colonoscopy.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Colosigmoid junction; Descending-sigmoid flexure; Large intestine; Large intestine flexures